Tilapia aquaculture, emerging diseases, and the roles of the skin microbiomes in health and disease - Debnath, Sanjit; McMurtrie, Jamie; Temperton, Ben; Delamare-Deboutteville, Jerome; Chadag, Vishnumurthy Mohan; Tyler, Charles (Springer, 2023)
Aquaculture is playing an increasingly important role in global food security, especially for low-income and food-deficit countries. The majority of aquaculture production occurs in freshwater earthen ponds and tilapia has quickly become one of the most widely adopted culture species in these systems. Tilapia are now farmed in over 140 countries facilitated by their ease of production, adaptability to a wide range of environmental conditions, fast growth, and high nutritional value. Typically, tilapia have been considered a hardy, disease resilient species; however, the disease is increasing with subsequent threats to the industry as their production is intensified. In this review, we discuss tilapia production, with a focus on Bangladesh as one of the top producing countries, and highlight the problems associated with disease and treatment approaches for them, including the misuse of antimicrobials. We address a key missing component in understanding health and disease processes for sustainable production in aquaculture, specifically the role played by the microbiome. Here we examine the importance of the microbiome in supporting health, focused on the symbiotic microbial community of the fish skin mucosal surface, the abiotic and biotic factors that influence the microbiome, and the shifts that are associated with diseased states. We also identify conserved taxa of skin microbiomes that may be used as indicators of health status for tilapia offering new opportunities to mitigate and manage the disease and optimize environmental growing conditions and farming practices.